Legalitas Kewenangan Penuntutan Tindak Pidana Pencucian Uang yang Dilakukan oleh Komisi Pemberantasan Tindak Pidana Korupsi dalam Sistem Peradilan Pidana - Doso, Musram; Arifin, Zainul (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2024)
This article aims to analyze the legality of the Corruption Eradication Commission’s (KPK) authority in prosecuting money laundering crimes (TPPU) derived from corruption offenses within Indonesia’s criminal justice system. This study contributes to providing an understanding of the legal basis, scope of authority, and the juridical and practical implications of such authority on the effectiveness of corruption eradication and inter-agency coordination among law enforcement institutions. This article falls under qualitative library research. The methodology used is a normative juridical study with a statute approach and a conceptual approach. The findings indicate that although the KPK has the authority to handle TPPU cases related to corruption offenses, there is an ongoing legal debate regarding overlapping authority with the Attorney General’s Office, potentially leading to institutional conflicts within the criminal justice system. Therefore, regulatory strengthening and coordination mechanisms among institutions are necessary to ensure the effective enforcement of laws against corruption and TPPU.